Phytoremediation of Sembrong River waters using neptunia oleracea and pistia stratiotes - Mohamed B. E. Bogelil, Mohamed B. E. (2017)
Water quality of Sungai Sembrong is in poor condition but it is an important source of water for people in Parit Raja. Water has to be treated intensively resulting in high cost. This study aims to determine the water quality index (WQI) and the efficiency of phytoremediation as well as the effect on the two plant species (Neptunia oleracea and Pistia stratiotes) due to bio mineralization of heavy metals. Water quality parameters measured were conductivity, turbidity, pH, Dissolved Oxygen (DO), Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), NH3N, TP, Zn, Fe, and Al. From this study, Sungai Sembrong is classified as Class IV according to DOE-WQI. Elements with high concentration were Al (61mg/L), Fe (33mg/L), and Zn (1.5mg/L) making it one of the most contaminated river in Malaysia. The condition for the water quality of the river was related to various land use along the river banks. N. oleracea performed better because for example on day 10 the COD is 60 mg/L as compared to P. stratiotes with COD at 78 mg/L N. oleracea was also in good condition for longer period of time. Uptake of the three trace elements (Al, Fe and Zn) in plants tissues were shown using AAS. The concentration of elements in plant tissue that were cultivated in river water were up to 254 times higher than the control plants except for Zn. Results of the biological studies suggested that the plants could be used for phytostabilization and phytoextraction of Al and Fe. However, the plants were not hyperaccumulators of Zn. Using photomicrography transverse sections of plant tissues cultivated in river water showed toxic symptoms like distortion, increase in the number of layers of cells and damages. The control plants did not exhibit any symptoms of damage. SEM-EDS analysis showed bio mineralized heavy metals distribution in different plant tissues which was supported by results from morpho-anatomical changes. The study concluded that cheaper ways of water treatment could be possible with the two species; N. oleracea and P. stratiotes.